Remarks on the shooting method for nonlinear two-point boundary-value problems - Nguyen, Trung Hieu (H. : ĐHQGHN, 2017)
In this note, we prove a convergent theorem for the shooting method combining the explicit Euler's scheme with the Newton method for solving nonlinear two-point boundary problems (TPBVPs). Some illustrative numerical examples are also considered.